Choice of Intermediary for Leisure Travel Arrangements - Ezeuduji, Ikechukwu O. (Journal of Economics and Behavioral Studies, 2015)
Travellers can plan and arrange holidays themselves online or through the supplier, or use the services of a travel organizer, such as a travel agent. Consumers of travel services will seek to optimize choices by selecting a distribution channel which will provide them with the greatest perceived value. The primary goal of this study is to explore the underlying factors that influence consumer behaviour in making travel decisions, with specific reference to choosing between booking through a travel agent or online. Research with a perspective on travel decision-making in South Africa is limited. This study surveyed 408 respondents residing in South Africa using a structured questionnaire examining preference in booking holiday flights or accommodation through a travel agent or Internet. Exploratory factor analysis was used to identify factors influencing traveller decision-making. Factors that influence travel decision-making were identified to include ‘trust’, ‘convenience and adoption of technology’, ‘best deal and price’, and ‘personal contact’. Travellers who preferred booking through the Internet found the potential of technology to save time and effort and to be convenient, due to the Internet being available day and night, important advantages of booking online. Travellers who preferred booking through a travel agent placed a premium on personal contact and social interaction between traveller and travel agent. They further valued the travel experience and ability of the travel agent to group transactions.